Bursuram, musicien des dieux en Inde centrale - Nicolas Prévôt (Terrains/Théories)
Through the figure of Bursuram, this article deals with the status, role and category of ritual specialists, in particular among the musicians of the Ganda caste in the Bastar region of Middle India. These musicians play for weddings and for possession rituals, and are often diviner, healer and medium as well. They live, not on their ritual skills, but on agriculture and daily labor made of varied heavy works. These religious activities which they carry out somehow as a part-time job, both out of devotion, out of social duty, as well as for fear of the gods and for pleasure, make them specialists of the invisible world. This article describes the multiplicity of their roles and identities, showing how they switch constantly and almost daily from one activity to another. While describing the relationship between music and possession in what is nothing else than a local form of Hinduism, it highlights the transitions, shifts, transformations and fluidity that equally characterize the way of life of these officiants, their cosmology and the entities that constitute it, starting with the shawm, a god-instrument with a variable identity. It also underlines the paradox between, on the one hand, the low status and impurity conferred on musicians, and, on the other hand, the central role and ritual power entrusted to them through music. Indeed, to perform the music of the gods comes down to interpreting possession by guessing who is Who, and to judging its authenticity. Located at the (sound) meeting point between the visible and the invisible, the musician passes – himself or the others – from one world to another. Whether as a musician or as a medium, he maintains this close link between men and the invisible world, making the gods and ancestors suddenly audible and visible.